2023
DOI: 10.1200/jco.2023.41.6_suppl.678
|View full text |Cite
|
Sign up to set email alerts
|

Association between time-of-day of the immune checkpoint inhibitor (ICI) infusion and disease outcomes among patients with metastatic renal cell carcinoma (mRCC).

Abstract: 678 Background: Recent studies have suggested an association between the time-of-day of ICI infusions and disease outcomes, including progression free survival and overall survival, among patients with cancer. (Qian et al Lancet Oncology 2021). We sought to identify whether such an association exists in patients with mRCC receiving ICIs. Methods: Patients with mRCC treated with nivolumab alone, or in combination with ipilimumab, in either first- or second-line treatment were retrospectively identified. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In metastatic melanoma, the MEMOIR retrospective study first documented a potential effect of circadian timing of the administration of immunotherapy (specifically ipilimumab, nivolumab, and pembrolizumab). The authors find that patients who received more than 20% of infusions after 4:30 p.m. had worse OS outcomes (HR of 2.04) [ 28 ]. Karaboué et al analyzed the impact of nivolumab administration timing in NSCLC using the median clock hour of a patient’s treatments and dichotomizing patients into AM (morning) and PM (afternoon) groups according to the period in which they received the most treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In metastatic melanoma, the MEMOIR retrospective study first documented a potential effect of circadian timing of the administration of immunotherapy (specifically ipilimumab, nivolumab, and pembrolizumab). The authors find that patients who received more than 20% of infusions after 4:30 p.m. had worse OS outcomes (HR of 2.04) [ 28 ]. Karaboué et al analyzed the impact of nivolumab administration timing in NSCLC using the median clock hour of a patient’s treatments and dichotomizing patients into AM (morning) and PM (afternoon) groups according to the period in which they received the most treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support these results while also providing evidence that allocation to a treatment group is balanced across observables and is, therefore, unlikely to be driving our results. Finally, in metastatic renal cell carcinoma, a correlation has been found between daytime administration of immunotherapy and OS favoring morning infusions [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those patients receiving 20% or more ICI infusions after 16:30 experienced worse OS (HR = 3.1 [1.27-7.36] (p = 0.01), shorter time on treatment (HR = 2.5 [1.21-4.99] (p = 0.013) and shorter time to next treatment line (HR = 1.9, [0.96-3.71] (p = 0.067) as compared to those who received less than 20% of the infusions after 16:30. In 145 patients treated with nivolumab alone, or in combination with ipilimumab as firstor second-line treatment for metastatic RCC, Dizman et al [28] showed consistent trends towards improved response rate, prolonged time-to-treatment failure, and OS among those patients receiving less than 25% of ICI infusions after 16:30.…”
Section: Tod Of Immunotherapy For Metastatic Malignant Melanoma Patientsmentioning
confidence: 95%
“…Additional retrospective studies on melanoma, NSCLC, squamous cell carcinoma of the esophagus, and renal cell carcinoma provide additional information on the role of the circadian rhythm in immunotherapy efficacy. Later infusion times have been associated with worse outcomes in renal cell carcinoma ( 92 ). One study on renal cell carcinoma found a continuous association with the number of treatments, finding a 16% increased risk of death for every 10% of infusions after 4:30 PM ( 93 ).…”
Section: Interventions and Circumstances To Consider Avoiding With Ic...mentioning
confidence: 99%